INVESTIGATING EFL TEACHERS’ APPROACHES TO MEANINGFUL LEARNING IN BLENDED-LEARNING LISTENING AND SPEAKING COURSES - Rahmawati, Fitria (Indonesian EFL Journal, 2022)
This study explored the approaches applied by EFL teachers to create meaningful learning activities to teach listening and speaking skills in a blended learning context and investigated some contributing factors in implementing the activities. Six EFL teachers with a diverse length of teaching experiences were purposively selected as the participants of this study. A case study was adopted as the research design involving several data-gathering techniques, including in-depth interview, document analysis, and observation. The study revealed some approaches implemented by the EFL teacher-participants to facilitate meaningful learning activities to teach listening and speaking skills in a blended learning context, both in the offline and online delivery modes. In addition, drawing inferences from the data, some factors became considerations by the teachers in selecting instructional approaches to be implemented to teach both English skills in a blended learning context. The study’s findings suggest the need for EFL teachers to carefully select and implement meaningful learning activities in a blended learning context specifically for teaching listening and speaking skills to assist student learning and provide better learning outcomes.Keywords: blended learning; in-class learning; out-class learning; listening and speaking skills; instructional activities; contributing factors